2011
DOI: 10.1051/0004-6361/200912916
|View full text |Cite
|
Sign up to set email alerts
|

Dense gas and the nature of the outflows

Abstract: We present the results of the observations of the (J, K) = (1, 1) and the (J, K) = (2, 2) inversion transitions of the NH 3 molecule toward a large sample of 40 regions with molecular or optical outflows, using the 37 m radio telescope of the Haystack Observatory. We detected NH 3 emission in 27 of the observed regions, which we mapped in 25 of them. Additionally, we searched for the 6 16 −5 23 H 2 O maser line toward six regions, detecting H 2 O maser emission in two of them, HH265 and AFGL 5173. We estimate … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 178 publications
(251 reference statements)
4
30
0
Order By: Relevance
“…The most intense emission in the central region of the 1.2‐mm dust continuum map is contained inside the HPBW of the low angular resolution NH 3 map of Sepúlveda et al (). The BIMA observations of MGE03 also only detected N 2 H + emission in a region almost coinciding with CL1/SMM5 (the other dust continuum sources lie outside the BIMA primary beam).…”
Section: Discussionmentioning
confidence: 94%
“…The most intense emission in the central region of the 1.2‐mm dust continuum map is contained inside the HPBW of the low angular resolution NH 3 map of Sepúlveda et al (). The BIMA observations of MGE03 also only detected N 2 H + emission in a region almost coinciding with CL1/SMM5 (the other dust continuum sources lie outside the BIMA primary beam).…”
Section: Discussionmentioning
confidence: 94%
“…References. (1) Mardones et al (1997); (2) Tafalla et al (2004); (3) Marcaide et al (1988); (4) Wiseman et al (2001); (5) Choi et al (1999); (6) Sepúlveda et al (2011); (7) Bourke et al (1995); (8) Bjerkeli et al (2011); (9) Fuente et al (2005); (10) Lefloch et al (1996). These observations, from now on referred to as the "557 GHz" observations, were made initially in position-switching (PS) mode using a reference 10 or more away from the source. Experience within the WISH project, however, showed that dual beam switching (DBS) with a 3 chop produced flatter baselines than PS, and the observing mode was changed to DBS after the first set of data were obtained.…”
Section: Hifi Observations Of Hmentioning
confidence: 99%
“…Heavily destroyed in UV fields (e.g. Fuente et al 1990, and references therein), it is present in cold dark clouds (Jijina et al 1999;Sepúlveda et al 2011) and also in regions affected by shocks (Tafalla & Bachiller 1995;Zhang et al 2002;Palau et al 2007). Since the very beginnings of molecular spectroscopy, it has been widely recognized as an excellent thermometer of the ISM (Ho & Townes 1983;Guesten et al 1985;Maret et al 2009).…”
Section: Derivation Of Physical Parametersmentioning
confidence: 99%